2016
DOI: 10.4236/ojst.2016.612032
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Masticatory Function Affects Growth and Development of the Mandibular Condyle in Rats

Abstract: The effects of childhood masticatory function loss and soft foods on the mandibular condyle have been the subject of much research. However, the corresponding bone turnover is not fully understood. The purpose of the present study was to clarify the effects of a lack of teeth and a soft food diet during the growth period on bone turnover in the mandibular condyle. We divided 3-week-old Wistar rats into the following three groups: 1) Extraction group: The maxillary molars were extracted at the age of 4 weeks, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 17 publications
(18 reference statements)
1
9
0
Order By: Relevance
“…Rats exhibit a smaller mandibular condyle and thinner cartilage when fed a soft diet during growth (Kato et al, 2015). Previous studies have reported that there was a regressive change in the trabecular structure when being fed a soft diet, which can reduce the resistance of the mandibular condyle to mechanical loading, and increase the occurrence temporomandibular deformation (Ogawa et al, 2016;Kono et al, 2017). In addition, alterations in occlusal stimuli followed by consumption of a soft diet may result in a decrease in the response of the mechanoreceptors of the temporomandibular joint (Ishida et al, 2009).…”
Section: Effects Of Low Occlusal Loading On Cortically-induced Jaw Movementsmentioning
confidence: 99%
“…Rats exhibit a smaller mandibular condyle and thinner cartilage when fed a soft diet during growth (Kato et al, 2015). Previous studies have reported that there was a regressive change in the trabecular structure when being fed a soft diet, which can reduce the resistance of the mandibular condyle to mechanical loading, and increase the occurrence temporomandibular deformation (Ogawa et al, 2016;Kono et al, 2017). In addition, alterations in occlusal stimuli followed by consumption of a soft diet may result in a decrease in the response of the mechanoreceptors of the temporomandibular joint (Ishida et al, 2009).…”
Section: Effects Of Low Occlusal Loading On Cortically-induced Jaw Movementsmentioning
confidence: 99%
“…Soft diet and molar extraction are conditions leading to a lower masticatory function. 12,19,20 Although it has not been verified in this study, based on other studies, [20][21][22][27][28][29]32 we assumed that extracting the maxillary right molars of young and adult rats could create a unilateral masticatory function, which in turn could cause changes to the condylar process.…”
Section: Discussionmentioning
confidence: 71%
“…Young rats were 4 weeks old, which corresponds to the initial period of usage of the teeth, which finish erupting at 21 days, 36 while adult rats were 26 weeks old. Many studies report similar ages when evaluating young and adult rats 10–18,21,22,27–29,31,32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, our previous research showed masticatory hypofunction in rats, due to extraction of maxillary molars and a diet of powdered feed, was associated with reduced mandibular volume, bone density, mandibular height, and mandibular condyle thickness [7] [8]. Additionally, we indicated that reduced masticatory function led to deformation and cellular disorders in the condylar cartilage, and diminished ossification and heightened bone resorption in the secondary cancellous bone of the condylar head, resulting in slower ossification, less bone volume, and reduced trabecular thickness [9]. There are also reports on the effects of occlusal stimuli on the alveolar bone: In rats, a soft diet, tooth extraction or the insertion of a bite-opening appliance were associated with a thinner [10] [11] [12] [13] and higher alveolar process [6] [10] [13] [14] [15], and sparser mandibular alveolar architecture [15] [ 16].…”
Section: Introductionmentioning
confidence: 71%